Identity. The demand for dignity and the politics of resentment - Velasco Martínez, Luis (Journal of the Spanish Institute for Strategic Studies, 2020)
Review of Fukuyama, Francis: Identity. The demand for dignity and the politics of resentment, Main, Profile Books, 2018, pp.208 18,24€